Risk of Prolonged Opioid Use Among Opioid-Naïve Patients After Common Shoulder Arthroscopy Procedures. Issue 5 (April 2019) - Gil, Joseph A.; Gunaseelan, Vidhya; DeFroda, Steven F.; Brummett, Chad M.; Bedi, Asheesh; Waljee, Jennifer F.
Background: Opioid-related morbidity and mortality are major public health concerns, and the risk of long-term opioid use after shoulder arthroscopy is not well defined. Hypothesis: Substance abuse disorders, pain disorders, and psychiatric conditions increase the risk for prolonged opioid use. Study Design: Case-control study, Level of evidence, 3. Methods: Insurance claims data from the Truven Health MarketScan Research Databases was used to identify patients who underwent shoulder arthroscopy between January 1, 2010, and March 31, 2015. Opioid-naïve patients were included. New prolonged opioid use was defined as continued opioid use between 91 and 180 days after the index procedure. The authors used a multivariable logistic regression model to identify patient factors associated with the risk of new prolonged opioid use. Results: In this cohort of 104, 154 opioid-naïve adult patients, 8686 (8.3%) developed new prolonged opioid use as defined in this study. A total of 31, 768 (30.5%) filled an opioid prescription in the 30 days before surgery. Patients who had limited debridement had the highest prolonged use rate (9.0%), followed by rotator cuff repair (8.5%), anterior labrum lesion repair (8.5%), and extensive debridement (8.2%). Patient characteristics associated with the highest odds ratios (ORs) of prolonged opioid use included those who had a total opioid dose during the perioperative period that was ≥743 oral morphine equivalents (ie, at least 149 tablets of 5-mg hydrocodone) (OR, 2.0; 95% CI, 1.9-2.1), followed by patients with a suicide and self-harm disorder (OR, 2.0; 95% CI, 1.1-3.4), a history of alcohol dependence or abuse (OR, 1.6; 95% CI, 1.3-1.9), a mood disorder (OR, 1.3; 95% CI, 1.2-1.4), an opioid prescription filled in the 30 days before surgery (OR, 1.3; 95% CI, 1.2-1.4), female sex (OR, 1.3; 95% CI, 1.2-1.3), an anxiety disorder (OR, 1.2; 95% CI, 1.1-1.3), and a history of a pain diagnosis (OR, 1.2; 95% CI, 1.1-1.2). Conclusion: The risk of prolonged opioid use after arthroscopic shoulder procedures is 8.3%, and it is higher among women and among those with greater opioid use in the early postoperative period, mental health conditions, substance dependence and abuse, and preexisting pain disorders. Patients at high risk warrant close surveillance after surgery for early recognition and management.